Loose Part Based STEAM Learning Using Local Wisdom of East Manggarai - Mathilde Muhu; Nice Maylani Asril; Ketut Indra Purnomo (Universitas Pendidikan Ganesha, 2024)
Learning activities for early childhood that could be more optimal impact children's development, causing them to be less stimulated. Based on this, this research aims to analyze Loose Part Based STEAM Learning with East Manggarai Local Wisdom in early childhood. This type of research is qualitative research. The research method used is the case study method. The subjects in this research were 20 class B students. Data collection methods in this research are interviews, questionnaires, and documentation. The instruments used to collect data were observation guidelines and interviews. The research data analysis technique is a qualitative descriptive analysis using the Miles and Huberman Model data analysis. The research results show that first, loose part-based STEAM learning with East Manggarai local wisdom is simple, meaning that the activities implemented are how to introduce children to the surrounding culture and get them used to loving local culture. The two teachers design learning activities containing elements of local wisdom according to the theme, sub-theme of the activity, planning, facilitating, and evaluating. Third, the environment can be a learning resource using tools and materials from the child's environment. It was concluded that Loose Part Based STEAM Learning with East Manggarai Local Wisdom can stimulate young children.